Physical and genetic map of the chromosome of Lactococcus lactis subsp. lactis IL1403. - Le Bourgeois, P (1992)
A combined physical and genetic map of the chromosome of Lactococcus lactis subsp. lactis IL1403 was determined. We constructed a restriction map for the NotI, ApaI, and SmaI enzymes. The order of the restriction fragments was determined by using the randomly integrative plasmid pRL1 and by performing indirect end-labeling experiments. The strain IL1403 chromosome was found to be circular and 2,420 kb in size. A total of 24 chromosomal markers were mapped on the chromosome by performing hybridization experiments with gene probes for L. lactis and various other bacteria. Integration of pRC1-derived plasmids via homologous recombination allowed more precise location of some lactococcal genes and allowed us to determine the orientation of these genes on the chromosome. Recurrent sequences, such as insertion elements and rRNA gene (rrn) clusters, were also mapped. At least seven copies of IS1076 were present and were located on 50% of the chromosome. In contrast, no copy of ISS1RS was detected. Six ribosomal operons were found on the strain IL1403 chromosome; five were located on 16% of the chromosome and were transcribed in the same direction. A comparison of the physical maps of L. lactis subsp. lactis IL1403 and DL11 showed that these two strains are closely related and that the variable regions are located mainly near the rrn gene clusters. In contrast, despite major restriction pattern dissimilarities between L. lactis IL1403 and MG1363, the overall genetic organization of the genome seems to be conserved between these two strains.